Effects of Arctic Alaska Oil Development on Brant and Snow Geese - Truett, Joe C.; Miller, Mark E.; Kertell, Kenneth (ARCTIC, 1997)
Black brant (Branta bernicla nigricans) and lesser snow geese (Chen c. caerulescens) breeding in and near arctic Alaska oil fields could be affected by oil development actions such as releases of contaminants, alteration of tundra surfaces, creation of impoundments, and human activities. These actions could affect geese directly (e.g., through oil spills) or indirectly (e.g., by altering food supplies or predator populations). Studies to date indicate no changes in the distribution, abundance, or reproduction of these geese that clearly can be attributed to development; rather, their numbers and recruitment have responded in the oil fields, as elsewhere, mainly to weather and predation. When snowmelt in spring is later than usual, the birds postpone or forego nesting, with consequent diminishment in recruitment. Predation by arctic foxes (Alopex lagopus), glaucous gulls (Larus hyperboreus), and grizzly bears (Ursus arctos) sometimes causes substantial losses of eggs and young, and predation by ravens (Corvus corax) has also been observed. Development-related changes in weather (microclimate) and loss of feeding habitat have involved small percentages of the total areas traditionally used, and populations of the birds probably have not been affected by these changes. Some studies and observations suggest that development has elevated local populations of some predators, but whether the level of predation on geese has in consequence risen above that which would have occurred in the absence of development is unknown; further investigation of this mechanism of potential impact is recommended. La bernache noire (Branta bernicla nigricans) et la petite oie des neiges (Chen c. caerulescens) nichant dans les champs pétrolifères de l'Alaska ou à proximité pourraient être affectées par des actes reliés à l'exploitation pétrolière, tels que le déversement d'agents de pollution, les modifications à la toundra de surface, la création de bassins, et par l'activité humaine. Ces interventions pourraient affecter les oies de ...